2015
DOI: 10.1063/1.4919455
|View full text |Cite
|
Sign up to set email alerts
|

An in-situ neutron diffraction study of a multi-phase transformation and twinning-induced plasticity steel during cyclic loading

Abstract: In-situ neutron diffraction during cyclic tension-compression loading (∼+3.5% to −2.8%) of a 17Mn-3Al-2Si-1Ni-0.06C steel that exhibits concurrent transformation and twinning -induced plasticity effects indicated a significant contribution of intragranular back stresses to the observed Bauschinger effect. Rietveld analysis revealed a higher rate of martensitic transformation during tension compared to compression. Throughout cycling, α′-martensite exhibited the highest phase strains such that it bears an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…The uniaxial tension of γ resulted in the typical development of a relatively stronger 111γ and a weaker 100γ double‐fiber texture parallel to the tensile axis comprising the Brass (Br γ , {110}112γ), Cu γ , and G γ orientations. Similar texture development was reported for an Fe–18.4Mn–3.2Si–3Al steel subjected to uniaxial tension up to 0.4 true strain and an Fe–17Mn–3Al–2Si steel cycled between +0.035 and −0.028 true strains. The evolution of the relatively strong 111γ and weak 100γ fibers were ascribed to the increase in the latent hardening on the non‐coplanar systems, which in turn promotes coplanar slip and resulted in an overall weakening of the 100γ fiber …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The uniaxial tension of γ resulted in the typical development of a relatively stronger 111γ and a weaker 100γ double‐fiber texture parallel to the tensile axis comprising the Brass (Br γ , {110}112γ), Cu γ , and G γ orientations. Similar texture development was reported for an Fe–18.4Mn–3.2Si–3Al steel subjected to uniaxial tension up to 0.4 true strain and an Fe–17Mn–3Al–2Si steel cycled between +0.035 and −0.028 true strains. The evolution of the relatively strong 111γ and weak 100γ fibers were ascribed to the increase in the latent hardening on the non‐coplanar systems, which in turn promotes coplanar slip and resulted in an overall weakening of the 100γ fiber …”
Section: Resultssupporting
confidence: 81%
“…Gazder et al showed the presence of stacking faults in ϵ ‐martensite by correlative transmission Kikuchi diffraction/transmission electron microscopy and suggested the deformation accommodation in ϵ ‐martensite. Using in situ tensile testing accompanied by neutron diffraction, Saleh et al demonstrated the ϵ ‐martensite to undertake compressive strains, which also indicated that ϵ ‐martensite accommodates deformation. During the plane strain compression of the present steel to 20% thickness reduction, the transformation of γ to deformation‐induced ϵ and α ′‐martensite was also observed without the formation of deformation‐induced twins in γ .…”
Section: Resultsmentioning
confidence: 99%
“…C 11 [GPa] C 22 [GPa] C 33 [GPa] C 12 [GPa] C 13 [GPa] C 23 [GPa] C 44 [GPa] On the out-necking area, the mesh with free structured tetrahedral element was used and the element seeds were assigned every 0.5 mm along the edge of the model. The same type of element was applied for the mesh of the in-necking area, but the distance between the element nodes was reduced to 0.05 mm in order to acquire a more accurate result along the necking zone.…”
Section: Mechanical Behaviour Inside the Necking Zonementioning
confidence: 99%
“…The main advantage of the diffraction methods is that the measurements are performed selectively only for the crystallites contributing to the measured diffraction peak. When several phases are present in the sample, measurements of a separate diffraction peak allows for investigating the behaviour of each phase independently [15][16][17][18][19][20][21][22][23][24][25]. A comparison of the diffraction data with micromechanical models is very convenient for the study of elastoplastic properties at micro and macro scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation